Is transport of microplastics different from mineral particles? Idealized wind tunnel studies on polyethylene microspheres - E. M. Esders; S. Sittl; I. Krammel; W. Babel; W. Babel; G. Papastavrou; C. K. Thomas; C. K. Thomas (Atmospheric Chemistry and Physics, 2023)
Atmospheric transport can disperse microplastic particulate matter to virtually every environment on the planet. Only a few studies have examined the fundamental transport mechanisms of microplastics and contrasted them with the existing body of knowledge accumulated on mineral dust over the past few decades. Our study addresses this research gap and presents results from idealized wind tunnel experiments, which examine the detachment behavior of microplastics ranging from 38 to 125 µm in diameter from smooth substrates. We here define detachment as microspheres detaching from a substrate and leaving the field of observation, which includes several transport modes, including creeping, rolling, and directly lifting off. The detachment behavior of polyethylene microspheres (PE69) and borosilicate microspheres (GL69) of nominally the same physical diameter (63–75 µm) is contrasted across hydrophilic to hydrophobic substrates. We further examine the effect of microsphere–microsphere collisions on the detachment behavior of both polyethylene and borosilicate microspheres. In a collision the rolling microsphere can detach a static microsphere or be stopped by it. Differentiating between microspheres experiencing only fluid forces and microspheres experiencing fluid forces and collisions revealed that collisions can facilitate and mitigate detachment. Further, results indicate that GL69, as a hydrophilic particle, is sensitive to substrate hydrophobicity, whereas PE69 is not sensitive. Sensitive microspheres detached more easily from hydrophobic substrates compared to hydrophilic substrates. The smallest polyethylene microspheres behave similarly to borosilicate microspheres. Results demonstrate that PE69 and GL69 as proxies for plastic and mineral dust, respectively, detach at u* between 0.1 and 0.3 m s−1, fitting the prediction of a fluid threshold model by Shao and Lu (2000). In the observed range of relative humidity (RH), capillary forces can increase the median detachment with about 0.2 m s−1 for PE69 and GL69. The smallest polyethylene microspheres behaved similarly to borosilicate microspheres by being sensitive to the substrate hydrophobicity. For bigger microspheres, the lesser density of polyethylene drives their higher erodibility. At a similar relative humidity, polyethylene microspheres detach at smaller friction velocities compared to borosilicate microspheres of the same nominal diameter. We argue that our idealized experiments provide a useful analog to more complex experiments, for example using simple soils as substrates. We conclude that plastic particles are preferentially transported, as their lower density and more hydrophobic surface facilitate detachment.